A IMPLEMENTAÇÃO DA BASE NACIONAL COMUM CURRICULAR (BNCC) E O IMPACTO SOBRE AS ATRIBUIÇÕES DO GESTOR ESCOLAR - Luis Carlos de Oliveira (2024)
This research had as its main objective, to analyze and understand the impact of the implementation of the National Common Curricular Base – BNCC on the duties of school managers, even causing changes in the profiles of these professionals due to the demands made by educational bodies to adapt them to the interests of the business community aligned with the State and educational institutions, as well as analyzing the requirements demanded by the educational system for the manager of public schools within the scope of the educational policies in progress in Brazil. The specific objectives of this research are to understand the characterization required of the profile of the educational manager with the implementation of the National Common Curricular Base, to analyze the set of legislation and guiding documents that direct the manager's performance in public schools in the State of São Paulo. Initially, we seek to present the scientific rationalization of work at the beginning of the 20th century (Fordism, Taylorism) and how these production systems required the training of workers. Next, I present the reconfiguration of labor relations, under the influence of Toyotism, which brought about a remodeling of labor relations, with the flexibility of means of production and qualified labor, focusing on quality management with more flexible methods and the use of technological resources established in management control and worker training. From this context, the research deals with the changes and implementations that occurred in the world of work under the strong influence of neoliberalism, a socioeconomic model created in the 20th century, in Europe, to guide Policies based on capitalism. Based on these discussions, the work seeks to present the restructuring of the means of production in Brazil, as well as the flexibilization of labor relations in the country and the transformations underway in the Brazilian educational system, especially regarding school agents and management. During the study, I seek to show the increased convergence between the government and business agendas and how much this is linked to a commodified vision of education, increasingly strengthening the movement to reform labor relations and the impact of these changes on the system. educational, undertaken in Brazil since the redemocratization process, with the introduction of a neoliberal policy in the country in the 1990s. The research sought to analyze the restructuring of labor relations based on Brazil's competitive experience in the global market, giving rise to a large productive restructuring in the country's industries in the last 30 years with the problematization of what are the requirements for the profile of the educational manager within the scope of the BNCC Policy implementation process and what are the political-pedagogical intentions that BNCC production agents require to educational managers as indicators of success in its implementation. This entire movement of restructuring new work relations, which has become more intensive in the last three decades, initiated a flow of new demands presented to school education in relation to its role as an educational institution, causing a series of changes to occur in the forms of management and organization of work at school. This new organization of work, implemented by educational reforms by the National Common Curricular Base (BNCC) through State-aligned domination apparatuses, results in the reconfiguration of the role and responsibilities of the manager and teachers in the school, as well as a heavier workload. intense situation that is leaving managers overwhelmed with the diverse daily demands, making work increasingly precarious.